2021
DOI: 10.3390/en14217058
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Shallow Geothermal Energy for Building Air-Conditioning

Abstract: Geothermal heat pumps have a widespread diffusion as they are able to deliver relatively higher energy output than other systems for building air-conditioning. The exploitation of low-enthalpy geothermal energy, however, presents crucial sustainability issues. This review investigates the primary forms of the environmental impact of geothermal heat pumps and the strategies for their mitigation. As life-cycle analyses shows that the highest impacts arise from installation and operation stages, most optimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 159 publications
(166 reference statements)
0
2
0
Order By: Relevance
“…The system's yearround capacity to deliver heating and cooling highlights its adaptability and applicability for various applications. The shallow geothermal system employing medium sandy soil appears to be operating effectively overall, and it is a promising technology for supplying heating and cooling sustainably and effectively [45].…”
Section: Carbon Pricingmentioning
confidence: 99%
“…The system's yearround capacity to deliver heating and cooling highlights its adaptability and applicability for various applications. The shallow geothermal system employing medium sandy soil appears to be operating effectively overall, and it is a promising technology for supplying heating and cooling sustainably and effectively [45].…”
Section: Carbon Pricingmentioning
confidence: 99%
“…Unlocking the energy and carbon savings potential of the building sector is closely linked with boosting the performance of new and existing buildings through a series of energy efficiency strategies. Since the biggest environmental impact is associated with the buildings' operational phase due to energy consumption for air conditioning (heating and cooling), efficient and sustainable technologies (such as, for instance, ground-source heat pumps [4]) represent promising solutions in this regard, but thermal insulation is certainly the widely recognized main strategy to reduce the overall energy demand. The strong correlation between the energy consumption of a building and its envelope characteristics is well known [5], as well as the contribution of insulated buildings in reducing air pollution and impacts on the environment [6].…”
Section: Introductionmentioning
confidence: 99%
“…The focus of researchers and engineers examining the sustainability of SGE systems is on system thermodynamics and the optimization of installation and operation stages, which can affect the energy exchange efficiency of SGE systems during the operation period. Andrea Aquino et al showed that the factors affecting the sustainability of SGE systems were mainly the climate and ground properties, the installation operations, and the maintenance of the refrigerant circuit and the serviced building, and the optimization of installation and operation stages can improve the SGE system [9]. Furthermore, the efficiency of the SGE system can be mainly controlled by the quality and quantity of the groundwater, the choice of aquifers and filter pipes, the distance between hot and cold wells, and the location of wells [10].…”
Section: Introductionmentioning
confidence: 99%